Pounding influence on adjacent linear elastic structures considering various impact simulation techniques - Mate, N. U.; Bakre, S.V.; Jaiswal, O.R. (Journal of Structural Engineering, 2024)
Damage due to pounding between adjacent structures is quite frequently seen in densely populated urban cities. The damage level varies from cosmetic to catastrophic for structures with insufficient separation. Now a days different models to simulate the pounding are available but they still have significant uncertainty in the collision properties which alter the final response of the structure. The collision force itself is highly dependent on the stiffness and damping of the ‘gap element’. In the present paper a comparative study of pounding forces obtained from various impact simulation models is made. The pounding models are made based upon the type of impact simulation technique used in gap element of adjacent structures. Total six impact simulation models have been prepared, gap element spring properties may be linear or non linear used in its mathematical formulation. These are applied on a system of three adjacent structures each one is considered as a linear single-degree-of-freedom (SDOF) system. It is observed that the impact forces in nonlinear spring models used for the gap elements by using Hertz, Hertz-damp and Nonlinear viscoelastic contact springs are getting lesser in magnitude than that of other linear spring models used for an impact simulation however the impact numbers are concerned, they are getting marginally same in all models.